Pesantren, the COVID-19 Pandemic and Digital Transformation: A Global Development Perspective - Supriyono, Supriyono (Muslim Education Review, 2022)
Scholarly debate on Islamic education lingers in a system that is often criticized for its reluctance to accept any forms of modernization, and this present study tries to prove the opposite. By exploring the dynamics of pesantren (Islamic boarding school) as an Islamic educational institution in coping with distance learning during the COVID-19 pandemic, this study observes the digital transformation made by pesantren during the time of the pandemic, and examines if this indicates development as per the concept of Sustainable Development Goals (SDGs). While SDG 4 suggests that the adoption of the Internet and computers is essential and becomes an indicator of quality education, locally it is debated whether the utilization of digital technology is compatible with pesantren values. Yet, this study argues that the pandemic situation—which requires distance learning—has forced pesantren to compromise in utilizing digital technologies. Different responses are made by pesantren depending on their institutional types: traditional, semi-traditional-modern, and modern. But significant improvement is reflected in how they have used digital technologies before and during the pandemic; either in their main pedagogical practice, or virtual study of yellow books (Kitab kuning), or in institutional and administrative matters. The discussion focuses on how—despite incompatibility in their values—digital adaptation could determine pesantrens’ survival and viability in the twenty-first century, by reflecting on how they survived the crisis during post-colonial times. In this case, not only does pesantrens’ digital adaptation satisfy the fulfillment of basic needs as in SDG 4, but it also helps them connect with the outside world, and further engage on issues within other SDGs. Overall, the study supports scholarly discussion on the resilience of faith-based education; that, despite the predicted collapse, it still manages to survive and adapt to modernity and development.